A Three-Phase, Five-Level Multilevel Inverter with Output Voltage Boost - N. Navaneetha, K. Divya, G. Greeshma, K. Prathyusha (Mathematical Statistician and Engineering Applications, 2022)
A three-phase full-bridge circuit with an added bidirectional switch has been used to generate 5-level output voltage by splitting a dc voltage source with two capacitors. The issue of voltage imbalance between the splitting capacitors and the limitation of the output voltage to the value of the input voltage source are both connected to this configuration. A unit topology for a five-level, three-phase MLI is proposed in this paper. It consists of an H-bridge circuit, a capacitor, a charge-discharge unit, and a dc source in each phase-leg. The interface between the H– bridge and the dc source is the charge discharge unit with the capacitor. The proposed unit cell can produce a phase leg output voltage waveform with five levels and a peak voltage twice as high as the input voltage; resulting in the creation of nine-level waveforms of the output line voltage. The proposed circuit's ability to boost output voltage is its most notable feature. The outcomes of the prototype and simulation experiments are presented